Invertebrate Biodiversity as Bioindicators of Sustainable Landscapes 1999
DOI: 10.1016/b978-0-444-50019-9.50020-0
|View full text |Cite
|
Sign up to set email alerts
|

Staphylinid beetles as bioindicators

Abstract: The family Staphylinidae is one of the largest beetle families and is distributed worldwide in almost all types of ecosystems. The morpho-ecological characteristics of staphylinid beetle adults and developmental stages are summarized, and features pertaining to their potential use as bioindicators are highlighted. Methods of study and practical examples are given for the application of staphylinids as bioindicators both in seminatural and cultural landscapes. The structure of staphylinid communities in biotope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0
6

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(80 citation statements)
references
References 15 publications
3
71
0
6
Order By: Relevance
“…1f; linear regression, P=0.0122; Kruskal-Wallis, P=0.0724), but showed a nonsignificant positive relationship with cicada carcass availability in days 14-21 (linear regression, P=0.0808; Kruskal-Wallis, P=0.3488). Nearly all known carabid and staphylinid beetles are polyphagous predators, though supplemental scavenging and detritus-associated predation is widespread in these diverse groups (Lovei and Sunderland 1996;Bohac 1999;Toft and Bilde 2002).…”
Section: Macroarthropod Detritivore Experimentsmentioning
confidence: 98%
“…1f; linear regression, P=0.0122; Kruskal-Wallis, P=0.0724), but showed a nonsignificant positive relationship with cicada carcass availability in days 14-21 (linear regression, P=0.0808; Kruskal-Wallis, P=0.3488). Nearly all known carabid and staphylinid beetles are polyphagous predators, though supplemental scavenging and detritus-associated predation is widespread in these diverse groups (Lovei and Sunderland 1996;Bohac 1999;Toft and Bilde 2002).…”
Section: Macroarthropod Detritivore Experimentsmentioning
confidence: 98%
“…As all life stages of S. erythropterus live in the topsoil litter layer, where most emitted metals end-up, they are exposed to pollution, especially considering the fact they absorb soil porewater and feed on animals recognized as macroconcentrators of metals. According to the review of Bohac (1999) Staphylinid larvae are considered more sensitive to pesticide and radionuclide pollution than imagos. However, Zvereva et al ( 2003) concluded that beetle larvae are less sensitive to metal pollution than adults because they are able to get rid of accumulated metals during molting.…”
Section: Staphylinus Erythropterusmentioning
confidence: 99%
“…Staphylinidae (Coleoptera) have been proposed as bioindicators or surrogates (Bohac 1999;Anderson and Ashe 2000;Pohl et al 2007) given that they are abundant and diverse (47,000 species); occupy a great variety of habitats worldwide; are easy to collect, given that the majority of the species are found among leaf litter and fallen trunks, forming one of the commonest groups of insects and ecologically the most important of the soil-related fauna; and the determination of the majority of the subfamilies is relatively well known (Bohac 1999;Navarrete-Heredia et al 2002;Newton et al 2005). In Colombia around 796 species and 230 genera of staphylinids are known, but some 5000 species are estimated, placing this family in a taxonomic information gap (Newton et al 2005).…”
Section: Introductionmentioning
confidence: 99%